Prevalence Of Narcissism In Adolescents Of Karachi - Qadir, Aisha; Naz, Lubna; Mushtaq, Samia; Zehra, Nazneen (Advances in Social Sciences Research Journal, 2019)
Narcissism may describe as be in love with own self. The individual may have variety of such behavior that are unfavorable for society such as rudeness, aggressive and violent behavior, selfishness, blaming and discourage others on their own faults, carelessness toward other feelings and emotions, inflated sense of supremacy and self-importance. More likely to involve in crimes and conflicts. Although Narcissistic personality disorder (NPD) is the serious issue but very little amount of work was done on this issue. The aim of this study is to evaluate the prevalence of narcissistic traits in the general youth population .The randomly selected sample of 1145 individuals falls in age group 18 to 25 were selected to estimate the prevalence of NPD .The Narcissistic Personality inventory (NPI-40) based on DSM III criteria was used to find out the prevalence of Narcissism in Study group. The result showed high scores of NPI in youth population167 male (47.44%) and 346 females (43.63%) scored >20 numbers in NPI. But NPI can only show relative idea of the frequency of narcissism, by scoring high in NPI it could not say certainly that individual lie in category of narcissistic so there is necessitate to more work should be done on this least studied topic to evaluate the true picture of narcissistic behavior in population.